Advances in water desalination - Lior, Noam. (Hoboken, N.J. : Wiley, 2012)
"Comprehensive coverage of desalination science, technology, economics, energy considerations, environmental impact, and more"--
1.F.10 Literature on Design ModelsCHAPTER 2 Environmental and Performance Aspects of Pretreatment and Desalination Technologies; 2.1 Introduction; 2.2 Global Desalination Capacity; 2.2.1 Capacity by Process Type and Source Water Type; 2.2.2 Capacity by Region and Source Water Type; 2.3 State of the Art of the Technology; 2.3.1 Seawater Intake; 2.3.2 Pretreatment Processes and Chemical Use; 2.3.3 Comparing Pretreatment Processes with Respect to Organic and Particulate Foulant Reductions in SWRO Systems; 2.3.4 Desalination Process and Energy Use; 2.3.5 Outfalls.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Saline water conversion; Saline water conversion -- Handbooks, manuals, etc; United States. Army -- Handbooks, manuals, etc; SCIENCE -- Chemistry -- Organic; Saline water conversion; Electronic books